2022
DOI: 10.1002/jmv.27629
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of the BNT162b2 COVID‐19 mRNA vaccine in PLWH: A monocentric study in Bari, Italy

Abstract: In March, people living with HIV infection (PLWH) were included in the risk category of fragile people for severe COVID‐19 receiving priority access to vaccination with BNT162b2 vaccine. The aim of the study was to evaluate the immunogenicity and safety of the two doses regimen. The antibodies titer for severe acute respiratory syndrome‐related coronavirus‐2 (SARS‐CoV‐2) was evaluated after 21 days since the first administration (Time 1), 1 (Time 2), and 3 (Time 3) months post‐vaccination. Information regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 18 publications
(54 reference statements)
5
41
1
Order By: Relevance
“…This might indicate an improved immune evasion of the Delta variant and raises concerns about the protection that two doses of mRNA vaccine mount in PLWH against current and upcoming variants of concern of SARS-CoV-2. Our results on the humoral immune response are in agreement with other reports that reported on immunogenicity and safety of COVID-19 vaccines 55, 56, 57 . In contrast, similar antibody responses were reported in a PLWH cohort that received an inactivated SARS-CoV-2 vaccine 58 .…”
Section: Discussionsupporting
confidence: 93%
“…This might indicate an improved immune evasion of the Delta variant and raises concerns about the protection that two doses of mRNA vaccine mount in PLWH against current and upcoming variants of concern of SARS-CoV-2. Our results on the humoral immune response are in agreement with other reports that reported on immunogenicity and safety of COVID-19 vaccines 55, 56, 57 . In contrast, similar antibody responses were reported in a PLWH cohort that received an inactivated SARS-CoV-2 vaccine 58 .…”
Section: Discussionsupporting
confidence: 93%
“…Our study is in line with several recent reports on HIV-1-infected individuals mounting robust spike-specific IgG antibody responses to vaccination with BNT162b2 mRNA, Moderna mRNA-1273 vaccine and ChAdOx1 nCoV-19 vaccines [ 5 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] comparable to healthy control groups in the majority of studies. Apart from spike-specific IgG, we were also able to detect spike-specific IgA in the serum of all vaccinated study subjects, demonstrating that the intramuscular application of the BNT162b2 mRNA vaccine can induce both IgA and IgG antibodies in HIV-1-infected subjects and in HIV-1-uninfected controls although at lower levels than IgG.…”
Section: Discussionsupporting
confidence: 92%
“…HIV or AIDs is classified as another independent risk factor for increased mortality due to COVID-19. Although it is suggested that immunocompromised individuals especially those with HIV be prioritized for the vaccine, due to the limited clinical data available for this demographic, there are still gaps in the knowledge regarding the efficacy of BNT162b2 in this cohort similar to those mentioned previously [ 33 ].…”
Section: Bnt162b2 Vaccination In At-risk Individualsmentioning
confidence: 80%
“…Efficacy of the vaccine in such patients is largely measured using CD4 + cell count, viral load, and disease stage [ 33 ]. According to a recently published prospective study including 143 HIV patients aged above 18 years and 261 healthy HCWs used as control, it was found that 18 days after the second dose of BNT162b2 vaccination, 98% (139/141) HIV patients had positive anti-receptor binding domain (RBD) IgG while 98.9% (258/261) HCWs had positive anti-RBD IgG 26 days after the second dose of BNT162b2 vaccine [ 34 ].…”
Section: Bnt162b2 Vaccination In At-risk Individualsmentioning
confidence: 99%